Transfer paper for laminating polaroid and preparation method of transfer paper

By using acrylate pressure-sensitive adhesives and antistatic agents in the polarizer bonding transfer paper, the existing silicone protective film is solved during the bonding process. The problem of poor buffering effect improves the fit quality and service life, ensuring the stability and consistency of the product.

CN119193035APending Publication Date: 2024-12-27SHANDONG TONGYOU NEW MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411685508.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-23
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing silicone protective film has poor buffering effect during the bonding process of polarizer and liquid crystal module, resulting in poor bonding and low product service life, affecting quality consistency and stability.

Method used

The antistatic foaming adsorption layer consisting of acrylate pressure-sensitive adhesive, physical foaming agent, antistatic agent and curing agent is used, and the antistatic substrate layer and the release layer are combined to produce high buffering and stable through the preparation method. for adhesive sheets.

Benefits of technology

The bond yield and service life of the polarizer and the liquid crystal module are improved, the quality consistency and stability of the product are ensured, and the impact of static electricity is reduced through anti-static function.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses transfer paper for polaroid lamination and a preparation method thereof, and relates to the technical field of polaroid production, and the transfer paper comprises a release layer, an antistatic foaming adsorption layer and an antistatic base material layer which are sequentially arranged from top to bottom. The prepared transfer paper not only has an antistatic function, but also has excellent buffering property and adsorbability due to the expansion microspheres with high foaming ratio.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polarizer production, and in particular to a transfer paper for polarizer lamination and a preparation method thereof. Background Art

[0002] Silicone protective films in polarizer laminating machines in the electronics industry are widely used for polarizer laminating liquid crystal modules. Chinese patent CN102815060B discloses a multi-layer adsorption sheet having a foamed resin layer with a thickness of 50μm to 500μm composed of acrylic foamed resin, and at least one PET film substrate layer laminated on the back of the foamed resin layer. Even if used for a long time in an environment with a curved portion, wrinkles and curling will not occur. However, this structure has a poor buffering effect during the lamination process of the polarizer and the liquid crystal module, which can easily cause poor lamination and a low product life, thus causing huge losses to customers and having a great impact on the quality consistency and stability of the product.

[0003] In view of the adverse problems existing in the silicone protective film on the market when used in polarizer lamination machines, a transfer paper for polarizer lamination is urgently needed. Summary of the invention

[0004] The first technical problem to be solved by the present invention is: in view of the shortcomings of the prior art, a transfer paper for polarizer lamination is provided, which has good cushioning properties and high product consistency and stability.

[0005] To solve the above-mentioned first technical problem, the technical solution of the present invention is: A transfer paper for polarizer lamination, comprising a release layer, an antistatic foaming adsorption layer and an antistatic substrate layer arranged in sequence from top to bottom; The antistatic foaming adsorption layer is composed of an acrylic pressure-sensitive adhesive, a physical foaming agent, an antistatic agent, a curing agent, and a diluent solvent in a weight ratio of 100: (4-10): (1-5): (0.5-3): (30-100); The physical foaming agent is expandable microspheres and the particle size of the microspheres is 5 to 40 μm; The antistatic agent is one of nano metal particles, carbon nano tubes and graphene.

[0006] Preferably, the antistatic substrate layer is one of PET film, PVC film, PEN film or PI film with an antistatic coating material coated on the surface, the thickness of the antistatic substrate layer is 50-150 μm, and the antistatic coating material is a polythiophene antistatic material.

[0007] Preferably, the release layer is a PET film coated with a non-silicone resin material, the coating thickness of the non-silicone resin material is 0.01-0.5 μm, and the thickness of the release layer is 25-150 μm.

[0008] Preferably, the acrylic pressure-sensitive adhesive is prepared by dissolving a main monomer and a functional monomer in an organic solvent, adding an initiator, and reacting under the condition of passing N2, and the mass content of each raw material is: Main monomer: 25-50% Functional monomer: 0.1-5% Initiator: 0.1-3% Organic solvents: 40-70%.

[0009] Preferably, the main monomer is any one of isooctyl acrylate, acrylic acid, cycloalkyl acrylate, n-butyl acrylate, methyl acrylate, n-hexyl acrylate or cycloalkyl methacrylate, or a mixture of two or more thereof.

[0010] Preferably, the functional monomer is any one of hydroxyethyl acrylate, acrylamide, dimethyl acrylamide or diethyl acrylamide, or a mixture of two or more thereof; The initiator comprises at least one of azobisisobutyronitrile, azobisisovaleronitrile, dimethyl azobisisobutyrate, dibenzoyl peroxide, tert-butyl peroxide (2-ethylhexanoate) or lauroyl peroxide; The organic solvent is any one of ethyl acetate, toluene, xylene and butanone, or a mixed solution of two or more thereof.

[0011] Preferably, the antistatic foaming adsorption layer has a thickness of 30-60 μm before foaming and a thickness of 60-150 μm after foaming.

[0012] Preferably, the curing agent is one or a mixture of two or more of isocyanate, polyisocyanate, polyamine, and glycidyl ether.

[0013] Preferably, the dilution solvent is one or a mixed solution of two or more of ethyl acetate, toluene, xylene and butanone.

[0014] The second technical problem to be solved by the present invention is: in view of the shortcomings of the prior art, a method for preparing transfer paper for polarizer lamination is provided, wherein the prepared transfer paper has good cushioning properties and high product consistency and stability.

[0015] To solve the above second technical problem, the technical solution of the present invention is: A method for preparing transfer paper for polarizer lamination comprises the following steps: S01. Preparation of acrylic pressure-sensitive adhesive S01-1, mixing the main monomer and the functional monomer to form a mixed monomer, taking 2 / 3 of the mixed monomer, and dissolving 1 / 4 of the weight of the initiator therein, fully dissolving to obtain a mixed solution; S01-2. Add 2 / 3 of the organic solvent to the reaction vessel, add the mixed solution therein, introduce nitrogen, stir and heat to 80-100°C, stir at a rate of 120-160 r / min, and react at a constant temperature for 1-3 hours; S01-3, continue to dropwise add the remaining mixed monomers and 1 / 2 weight of the initiator into the reaction vessel within 1 hour, and then react at a constant temperature for 1 to 2 hours; S01-4, then add the remaining initiator and the remaining organic solvent dropwise, react at a constant temperature for 1 to 2 hours, cool, and stop the reaction when the temperature drops to 30° C. to obtain an acrylate pressure-sensitive adhesive; S02. Preparation of antistatic foaming adsorption layer S02-1 The acrylic pressure-sensitive adhesive, antistatic agent, physical foaming agent, diluent and curing agent are stirred and mixed uniformly according to the weight ratio to prepare a foamable antistatic pressure-sensitive adhesive liquid; S02-2, filtering the foamable antistatic pressure-sensitive adhesive liquid obtained in step S02-1 through a 200-400 mesh filter screen, coating it on the antistatic substrate layer through a blade coater or a CED coater, drying it completely, attaching a release layer, and winding it up for aging to obtain an unfoamed transfer paper; S03. Preparation of transfer paper S03-1, the unfoamed transfer paper prepared in S02-2 is subjected to high temperature treatment to foam it and then embossed with different mesh sizes and shapes to prepare a transfer paper for polarizer lamination with foaming and adsorption function and having antistatic function.

[0016] Due to the adoption of the above technical solution, the beneficial effects of the present invention are: 1. The present invention adds expanded microspheres and carbon nanotubes to the prepared acrylic pressure-sensitive adhesive so that the prepared transfer paper not only has antistatic function but also has excellent cushioning and adsorption properties due to the expanded microspheres with high foaming ratio.

[0017] 2. The present invention prepares a uniform unfoamed material by a coating method, and after physical foaming in the latter stage, the foaming of the transfer paper is uniform and controllable.

[0018] 3. The present invention can achieve universality for polarizers of different sizes from different manufacturers by embossing meshes of different diameters on the surface of the foamed material and adjusting the adsorption force on the surface of the transfer paper.

[0019] 4. The antistatic foam transfer paper prepared by the present invention not only plays a bearing and buffering role in the process of laminating the polarizer and the liquid crystal module, but also the high rebound effect of the foaming layer can greatly improve the laminating yield of the liquid crystal module and the polarizer, and the service life of the transfer paper is also greatly improved due to the foaming buffering effect; secondly, the addition of carbon nanotube antistatic agent also makes the transfer paper antistatic, which can effectively eliminate static electricity in the process of laminating the polarizer and the liquid crystal module, and avoid the influence of static electricity on the liquid crystal module during the laminating and peeling process. DETAILED DESCRIPTION

[0020] The present invention will be further described below in conjunction with the embodiments. Example 1

[0021] A method for preparing transfer paper for polarizer lamination comprises the following steps: Preparation of acrylic pressure-sensitive adhesive 1. Based on the total amount of raw materials used in its preparation, the components include the following mass contents: main monomer (isooctyl acrylate) 22wt%, (n-butyl acrylate) 14.5wt%, functional monomer (hydroxyethyl acrylate) 0.3wt%, (dimethylacrylamide) 0.5wt%, initiator (azobisisobutyronitrile) 0.5wt%, organic solvent (ethyl acetate) 62.2wt%.

[0022] 1-1. According to the weight ratio, isooctyl acrylate, n-butyl acrylate, hydroxyethyl acrylate and dimethyl acrylamide are mixed to form a mixed monomer, 2 / 3 of the mixed monomer is taken, and azobisisobutyronitrile accounting for 1 / 4 of the total amount of the initiator is dissolved therein, and the mixture is fully dissolved to obtain a mixed solution; 1-2. In a four-necked flask equipped with a stirrer, a condenser, a nitrogen tube and a dropping funnel, add 2 / 3 of an organic solvent, and add the mixed solution in step 1-1 therein, introduce nitrogen, stir and heat to 80-100°C, at a stirring rate of 120-160 r / min, and react at a constant temperature for 1-3 hours; 1-3. Add the remaining mixed monomers and azobisisobutyronitrile accounting for 1 / 2 of the total amount of initiator dropwise within 1 hour, and then react at a constant temperature for 1 to 2 hours; 1-4, then add the remaining initiator azobisisobutyronitrile and the remaining organic solvent, react at a constant temperature for 1 to 2 hours to allow the unreacted monomers to react completely, cool, and stop the reaction when the temperature drops to 30° C. to obtain an acrylic pressure-sensitive adhesive; 2. Preparation of antistatic foaming adsorption layer 2-1 Add the prepared acrylic pressure-sensitive adhesive, foaming microspheres MSH-340 of Japan Oil, Suzhou Insai single-walled carbon nanotubes C501, Covestro isocyanate curing agent L75 and diluent solvent into a container at a mass ratio of 100:5:3:1:50, stir at 23°C and 300r / min for 30min until uniformly mixed, and filter twice with a 200-mesh filter to obtain a foamable anti-static pressure-sensitive adhesive solution; wherein the diluent solvent is a mixed solvent of toluene and ethyl acetate, and the solvent mass ratio is 1:1; 2-2. The foamable antistatic pressure-sensitive adhesive liquid obtained in step 2-1 is filtered and coated with a 50 μm adhesive layer on a 100 μm white antistatic PET substrate layer using a knife coater or a CED coater. After drying completely, a 50 μm release layer is attached and rolled up for aging to obtain an unfoamed transfer paper.

[0023] 3. Preparation of transfer paper The unfoamed transfer paper prepared in 2-2 is foamed by high temperature treatment and then embossed with a mesh shape of 2 mm in diameter to obtain a transfer paper with foaming and adsorption effect having antistatic function. Example 2

[0024] A method for preparing transfer paper for polarizer lamination comprises the following steps: Preparation of acrylic pressure-sensitive adhesive 1. Based on the total amount of raw materials used in its preparation, the components include the following mass contents: main monomer (acrylic acid) 18wt%, (cycloalkyl acrylate) 12wt%, functional monomer (acrylamide) 0.1wt%, initiator (azobisisovaleronitrile) 0.1wt%, organic solvent (toluene) 35wt%, (xylene) 34.8wt%.

[0025] 1-1. According to the weight ratio, acrylic acid, cycloalkyl acrylate and acrylamide are mixed to form a mixed monomer, 2 / 3 of the mixed monomer is taken, and azobisisovaleronitrile accounting for 1 / 4 of the total amount of the initiator is dissolved therein, and the mixture is fully dissolved to obtain a mixed solution; 1-2. In a four-necked flask equipped with a stirrer, a condenser, a nitrogen tube and a dropping funnel, add 2 / 3 of an organic solvent, and add the mixed solution in step 1-1 therein, introduce nitrogen, stir and heat to 80-100°C, at a stirring rate of 120-160 r / min, and react at a constant temperature for 1-3 hours; 1-3. Add the remaining mixed monomers and azobisisovaleronitrile accounting for 1 / 2 of the total amount of initiator dropwise within 1 hour, and then react at a constant temperature for 1 to 2 hours; 1-4, then add the remaining initiator azobisisovaleronitrile and the remaining organic solvent, react at a constant temperature for 1 to 2 hours to allow the unreacted monomers to react completely, cool, and stop the reaction when the temperature drops to 30° C. to obtain an acrylic pressure-sensitive adhesive; 2. Preparation of antistatic foaming adsorption layer 2-1 Add the prepared acrylic pressure-sensitive adhesive, foaming microspheres MSH-340 of Japan Oil, nano-metal particles DK101 of Zhongke Leiming, a mixed curing agent of polyisocyanate and polyamine, and a diluent solvent into a container at a mass ratio of 100:4:1:0.5:100, stir at 23°C and 300r / min for 30min until the mixture is uniformly mixed, and filter twice with a 200-mesh filter to obtain a foamable anti-static pressure-sensitive adhesive solution; wherein the diluent is butanone, and the mass ratio of polyisocyanate to polyamine in the mixed curing agent is 1:1; 2-2. Filter the foamable antistatic pressure-sensitive adhesive obtained in step 2-1 and apply 30 μm on a 50 μm white antistatic PVC substrate layer using a knife coater or a CED coater. After drying completely, attach a 150 μm release layer and roll up for aging to obtain unfoamed transfer paper.

[0026] 3. Preparation of transfer paper The unfoamed transfer paper prepared in 2-2 is foamed by high temperature treatment and then embossed with a mesh shape of 4 mm in diameter to obtain a foamed and adsorbent transfer paper with antistatic function. Example 3

[0027] A method for preparing transfer paper for polarizer lamination comprises the following steps: Preparation of acrylic pressure-sensitive adhesive 1. Based on the total amount of raw materials for its preparation, the components include the following mass contents: main monomer (methyl acrylate) 16wt%, (n-hexyl acrylate) 15wt%, (cycloalkyl methacrylate) 19wt%, functional monomer (diethyl acrylamide) 5wt%, initiator (dimethyl azobisisobutyrate) 1.5wt%, dibenzoyl peroxide 0.5wt%, tert-butyl peroxide (2-ethylhexanoate) 1wt%, organic solvent (toluene) 21wt%, (xylene) 21wt%.

[0028] 1-1. Methyl acrylate, n-hexyl acrylate, cycloalkyl methacrylate and diethyl acrylamide are mixed according to weight ratio to form a mixed monomer. 2 / 3 of the mixed monomer is taken and 1 / 4 of the total amount of initiator is dissolved therein and fully dissolved to obtain a mixed solution. 1-2. In a four-necked flask equipped with a stirrer, a condenser, a nitrogen tube and a dropping funnel, add 2 / 3 of an organic solvent, and add the mixed solution in step 1-1 therein, introduce nitrogen, stir and heat to 80-100°C, at a stirring rate of 120-160 r / min, and react at a constant temperature for 1-3 hours; 1-3. Add the remaining mixed monomers and 1 / 2 of the total amount of initiator dropwise within 1 hour, and then react at a constant temperature for 1 to 2 hours; 1-4, then add the remaining initiator and the remaining organic solvent, react at a constant temperature for 1 to 2 hours to allow the unreacted monomers to react completely, cool, and stop the reaction when the temperature drops to 30°C to obtain an acrylic pressure-sensitive adhesive; 2. Preparation of antistatic foaming adsorption layer 2-1 Add the prepared acrylic pressure-sensitive adhesive, foaming microspheres MSH-340 of Japan Oil, graphene slurry GX-G0-1 of Gaoxun Technology, glycidyl ether curing agent GA-240A and diluent solvent into a container at a mass ratio of 100:10:5:3:30, stir at 23°C and 300r / min for 30min until uniformly mixed, and filter twice with a 200-mesh filter to obtain a foamable anti-static pressure-sensitive adhesive solution; wherein the diluent solvent is xylene; 2-2. Filter the foamable antistatic pressure-sensitive adhesive obtained in step 2-1 and coat 60 μm on a 25 μm white antistatic PEN substrate layer using a knife coater or a CED coater. After drying completely, attach a 25 μm release layer and roll up for aging to obtain unfoamed transfer paper.

[0029] 3. Preparation of transfer paper The unfoamed transfer paper prepared in 2-2 is foamed by high temperature treatment and then embossed with a mesh shape of 2 mm in diameter to obtain a transfer paper with foaming and adsorption effect having antistatic function. Example 4

[0030] A method for preparing transfer paper for polarizer lamination comprises the following steps: Preparation of acrylic pressure-sensitive adhesive 1. Calculated by the total amount of raw materials for its preparation, the components include the following mass contents: main monomer (methyl acrylate) 25wt%, (n-butyl acrylate) 20wt%, functional monomer (hydroxyethyl acrylate) 0.3wt%, (dimethylacrylamide) 2.5wt%, initiator (lauroyl peroxide) 1.8wt%, organic solvent (butanone) 50.4wt%.

[0031] 1-1. Methyl acrylate, n-butyl acrylate, hydroxyethyl acrylate and dimethyl acrylamide are mixed according to weight ratio to form a mixed monomer. 2 / 3 of the mixed monomer is taken and lauroyl peroxide accounting for 1 / 4 of the total amount of the initiator is dissolved therein and fully dissolved to obtain a mixed solution. 1-2. In a four-necked flask equipped with a stirrer, a condenser, a nitrogen tube and a dropping funnel, add 2 / 3 of an organic solvent, and add the mixed solution in step 1-1 therein, introduce nitrogen, stir and heat to 80-100°C, at a stirring rate of 120-160 r / min, and react at a constant temperature for 1-3 hours; 1-3. Add the remaining mixed monomers and lauroyl peroxide accounting for 1 / 2 of the total amount of initiator dropwise within 1 hour, and then react at a constant temperature for 1 to 2 hours; 1-4, then add the remaining initiator lauroyl peroxide and the remaining organic solvent, react at a constant temperature for 1 to 2 hours to allow the unreacted monomers to react completely, cool, and stop the reaction when the temperature drops to 30° C. to obtain an acrylate pressure-sensitive adhesive; 2. Preparation of antistatic foaming adsorption layer 2-1 Add the prepared acrylic pressure-sensitive adhesive, foaming microspheres MSH-340 of Japan Oil, Suzhou Insai single-walled carbon nanotubes C501, Covestro isocyanate curing agent L75 and diluent solvent into a container at a mass ratio of 100:10:5:1.2:80, stir at 23°C and 300r / min for 30min until uniformly mixed, and filter twice with a 200-mesh filter to obtain a foamable anti-static pressure-sensitive adhesive solution; wherein the diluent solvent is a mixed solvent of toluene and butanone, and the solvent mass ratio is 1:1; 2-2. Filter the foamable antistatic pressure-sensitive adhesive obtained in step 2-1 and coat 50 μm on a 150 μm white antistatic PET substrate layer using a knife coater or a CED coater. After drying completely, attach an 80 μm release layer and roll up for aging to obtain unfoamed transfer paper.

[0032] 3. Preparation of transfer paper The unfoamed transfer paper prepared in 2-2 is foamed by high temperature treatment and then embossed with a mesh shape of 5 mm in diameter to obtain a transfer paper with foaming and adsorption effect having antistatic function. Example 5

[0033] A method for preparing transfer paper for polarizer lamination comprises the following steps: Preparation of acrylic pressure-sensitive adhesive 1. Based on the total amount of raw materials used in its preparation, the components include the following mass contents: main monomer (cycloalkyl acrylate) 18wt%, (cycloalkyl methacrylate) 17wt%, functional monomer (dimethylacrylamide) 1.2wt%, (diethylacrylamide) 1.1wt%, initiator (azobisisovaleronitrile) 1.8wt%, (dibenzoyl peroxide) 1.2wt%, organic solvent (butanone) 59.7wt%.

[0034] 1-1. According to the weight ratio, cycloalkyl acrylate, cycloalkyl methacrylate, dimethyl acrylamide and diethyl acrylamide are mixed to form a mixed monomer, 2 / 3 of the mixed monomer is taken, and 1 / 4 of the total amount of initiator is dissolved therein, and fully dissolved to obtain a mixed solution; 1-2. In a four-necked flask equipped with a stirrer, a condenser, a nitrogen tube and a dropping funnel, add 2 / 3 of an organic solvent, and add the mixed solution in step 1-1 therein, introduce nitrogen, stir and heat to 80-100°C, at a stirring rate of 120-160 r / min, and react at a constant temperature for 1-3 hours; 1-3. Add the remaining mixed monomers and 1 / 2 of the total initiator dropwise within 1 hour, and then react at a constant temperature for 1 to 2 hours; 1-4, then add the remaining initiator and the remaining organic solvent, react at a constant temperature for 1 to 2 hours to allow the unreacted monomers to react completely, cool, and stop the reaction when the temperature drops to 30°C to obtain an acrylic pressure-sensitive adhesive; 2. Preparation of antistatic foaming adsorption layer 2-1 Add the prepared acrylic pressure-sensitive adhesive, foaming microspheres F-77D of Japan Oil, single-walled carbon nanotubes GT2 of South Korea Gratube, isocyanate curing agent HT-100 of Wanhua and diluent solvent into a container in a mass ratio of 100:4:2:0.5:30, stir for 30 minutes at 23°C and 300r / min until the mixture is evenly mixed, and filter twice with a 200-mesh filter to obtain a foamable anti-static pressure-sensitive adhesive solution; wherein the diluent solvent is toluene; 2-2. Filter the foamable antistatic pressure-sensitive adhesive obtained in step 2-1 and coat 30 μm on a 50 μm white antistatic PI substrate layer using a knife coater or a CED coater. After drying completely, attach a 40 μm release layer and roll up for aging to obtain unfoamed transfer paper.

[0035] 3. Preparation of transfer paper The unfoamed transfer paper prepared in 2-2 is foamed by high temperature treatment and then embossed with a mesh shape with a diameter of 3 mm to obtain a transfer paper with foaming and adsorption effect having antistatic function. Comparative Example 1

[0036] The foamed microspheres MSH-340 were not added, and the rest were exactly the same as in Example 1. Comparative Example 2

[0037] No single-walled carbon nanotubes C501 were added, and the rest were exactly the same as in Example 1.

[0038] The product performances of the above-mentioned embodiments 1-5 and comparative examples 1-2 were tested respectively. The specific test items and test methods are shown in Table 1 below, and the test results are shown in Table 2.

[0039] Table 1

[0040] Table 2

[0041] It can be seen from the experimental data in the above table that an antistatic functional foaming material with low peel strength can be prepared by adding expanded microspheres and carbon nanotubes; the present invention not only makes the prepared transfer paper material have antistatic function by adding expanded microspheres and carbon nanotube materials to the acrylic pressure-sensitive adhesive, but also the foaming of the expanded microspheres makes the transfer paper have excellent cushioning properties; secondly, the adsorption of the transfer paper surface can be further adjusted by imprinting meshes of different diameters.

[0042] It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope limited by the appended claims of the application.

Claims

1. A transfer paper for polarizer lamination, characterized by: It includes a release layer, an antistatic foaming adsorption layer and an antistatic base material layer which are sequentially arranged on top of each other; The antistatic foaming adsorption layer is composed of an acrylic pressure-sensitive adhesive, a physical foaming agent, an antistatic agent, a curing agent, and a diluent solvent in a weight ratio of 100: (4-10): (1-5): (0.5-3): (30-100); The physical foaming agent is expandable microspheres with a particle size of 5 to 40 μm; The antistatic agent is one of nano metal particles, carbon nano tubes and graphene.

2. The transfer paper for polarizer lamination according to claim 1, wherein: The antistatic substrate layer is one of PET film, PVC film, PEN film or PI film with an antistatic coating material coated on the surface. The thickness of the antistatic substrate layer is 50-150 μm, and the antistatic coating material is a polythiophene antistatic material.

3. The transfer paper for polarizer lamination according to claim 1, wherein: The release layer is a PET film coated with a non-silicone resin material. The coating thickness of the non-silicone resin material is 0.01-0.5 μm. The thickness of the release layer is 25-150 μm.

4. The transfer paper for polarizer lamination according to claim 1, wherein: The acrylic pressure-sensitive adhesive is prepared by dissolving a main monomer and a functional monomer in an organic solvent, adding an initiator, and reacting under the condition of flowing N2. The mass content of each raw material is: Main monomer: 25-50% Functional monomer: 0.1-5% Initiator: 0.1-3% Organic solvents: 40-70%.

5. The transfer paper for polarizer lamination according to claim 4, wherein: The main monomer is any one of isooctyl acrylate, acrylic acid, cycloalkyl acrylate, n-butyl acrylate, methyl acrylate, n-hexyl acrylate or cycloalkyl methacrylate, or a mixture of two or more thereof.

6. The transfer paper for polarizer lamination according to claim 4, wherein: The functional monomer is any one of hydroxyethyl acrylate, acrylamide, dimethyl acrylamide or diethyl acrylamide, or a mixture of two or more thereof; The initiator comprises at least one of azobisisobutyronitrile, azobisisovaleronitrile, dimethyl azobisisobutyrate, dibenzoyl peroxide, tert-butyl peroxide (2-ethylhexanoate) or lauroyl peroxide; The organic solvent is any one of ethyl acetate, toluene, xylene, and butanone, or a mixed solution of two or more thereof.

7. The transfer paper for polarizer lamination according to claim 1, wherein: The thickness of the antistatic foaming adsorption layer before foaming is 30-60 μm, and the thickness after foaming is 60-150 μm.

8. The transfer paper for polarizer lamination according to claim 1, wherein: The curing agent is one or a mixture of two or more of isocyanate, polyisocyanate, polyamine, and glycidyl ether.

9. The transfer paper for polarizer lamination according to claim 1, wherein: The dilution solvent is one or a mixed solution of two or more of ethyl acetate, toluene, xylene and butanone.

10. The method for preparing transfer paper for polarizer lamination according to any one of claims 1 to 9, wherein: The following steps are involved: S01. Preparation of acrylic pressure-sensitive adhesive S01-1. Mix the main monomer and the functional monomer to form a mixed monomer, take 2 / 3 of the mixed monomer, and dissolve 1 / 4 of the initiator by weight therein, and fully dissolve to obtain a mixed solution; S01-2. Add 2 / 3 of the organic solvent to the reaction vessel, add the mixed solution thereto, introduce nitrogen, stir and heat to 80-100°C at a stirring rate of 120-160 r / min, and react at this constant temperature for 1-3 hours; S01-3, continue to dropwise add the remaining mixed monomers and 1 / 2 weight of the initiator into the reaction vessel within 1 hour, and then react at a constant temperature for 1 to 2 hours; S01-4, then add the remaining initiator and the remaining organic solvent dropwise, react at a constant temperature for 1 to 2 hours, cool, and stop the reaction when the temperature drops to 30° C. to obtain an acrylate pressure-sensitive adhesive; S02. Preparation of antistatic foaming adsorption layer S02-1: uniformly mixing an acrylic pressure-sensitive adhesive, an antistatic agent, a physical foaming agent, a diluent, and a curing agent according to a weight ratio to prepare a foamable antistatic pressure-sensitive adhesive solution; S02-2. The foamable antistatic pressure-sensitive adhesive prepared in step S02-1 is filtered through a 200-400 mesh filter, coated on the antistatic substrate using a knife coater or a CED coater, dried completely, and then attached with a release layer, rolled up, and aged to produce unfoamed transfer paper. S03. Preparation of transfer paper S03-1, subjecting the unfoamed transfer paper prepared in S02-2 to high-temperature treatment for foaming and embossing with different mesh sizes and shapes to prepare transfer paper for polarizer lamination with foaming and adsorption properties and having antistatic function.

Citation Information

Patent Citations

  • Cutting adhesive tape for processing semiconductor materials, and preparation method thereof

    CN110205043A

  • UV viscosity-reducing protective film and manufacturing method thereof

    CN112920731A

  • Adhesive with low antistatic agent precipitation, polaroid protective film and preparation method of polaroid protective film

    CN118185497A